2013
DOI: 10.4028/www.scientific.net/amr.664.27
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Yangtze River and Yellow River Paleochannels in South Yellow Sea Shelf

Abstract: research of submarine paleochannels has not only a great significance in exploring the evolution of palaeoenvironment of continental shelf but also a practical application value in solving problems on disaster geology and environmental geology in the continental shelf development. Yellow River and Yangtze River both were concentrated in the northern Jiangsu to enter the South Yellow Sea Basin in the Last Glacial, playing an important role in the palaeoenvironment evolution of the South Yellow Sea. On the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Therefore, under the action of the Coriolis force, the relatively strong winter monsoon effect makes the southward transport volume of sediment greater than the northward transport volume. As a result, the southern part of the Yellow River subaqueous delta (the eastern and southeastern part of Laizhou Bay) had fine-grained sediments transported by the Yellow River [41], while the northern part developed erosive landforms [42], presenting a "south deposition and north erosion" model. The critical erosion stress of the Yellow River delta is about 0.30 Pa [43].…”
Section: The Characteristics Of Erosion and Deposition In The Yellow ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, under the action of the Coriolis force, the relatively strong winter monsoon effect makes the southward transport volume of sediment greater than the northward transport volume. As a result, the southern part of the Yellow River subaqueous delta (the eastern and southeastern part of Laizhou Bay) had fine-grained sediments transported by the Yellow River [41], while the northern part developed erosive landforms [42], presenting a "south deposition and north erosion" model. The critical erosion stress of the Yellow River delta is about 0.30 Pa [43].…”
Section: The Characteristics Of Erosion and Deposition In The Yellow ...mentioning
confidence: 99%
“…The evolution trend shows a trend of accumulation in the north and erosion in the south. The sand ridges are dominated by tidal currents and are mainly distributed at the southern part of Subei Shoal in the northern part of the Yangtze River subaqueous delta and the southeastern outer edge of the delta [42]. The bottom bed changes in the Yangtze River mouth are mainly characterised by "channel erosion and shoal accumulation", "near-shore (depth < 6.4 m) accumulation and far-shore (6.4 m < depth < 19 m) erosion" outside the mouth, and the accumulation pattern appears as "southern erosion and northerly accumulation" [44].…”
Section: The Characteristics Of Erosion and Deposition In The Yangtze...mentioning
confidence: 99%
“…Previous results also revealed differences in carbonate mineral contents [11][12][13][14], crystal shapes [12], grain size effects [12], abrasion and dissolution characteristics [15], etc., which could be used as tracing indices of the Yangtze River and Yellow River [11] to indicate the provenance of sediments on the continental shelf [12]. Other studies have suggested that indicators such as the crystal shape [16], light and/or heavy mineral assemblages [4,11,17,18], geochemical composition [5,6,19,20], magnetite content and other magnetic parameters [2,21,22] could also be applied to distinguish these two large rivers and the sediment provenance [4,5,17,23] of the Yellow Sea and East Sea. In addition, previous results indicated that Yellow River sediments were characterized by high mica mineral contents [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the results demonstrated that differences between the sediments in these two large rivers could be found in terms of clay mineral contents [6][7][8], ratios [9], crystallinity [7,9], chemical indices [9], crystal shapes [10], geochemical characteristics [10], etc., including indicators of detritus identification [7,8]. Previous results also revealed differences in carbonate mineral contents [11][12][13][14], crystal shapes [12], grain size effects [12], abrasion and dissolution characteristics [15], etc., which could be used as tracing indices of the Yangtze River and Yellow River [11] to indicate the provenance of sediments on the continental shelf [12]. Other studies have suggested that indicators such as the crystal shape [16], light and/or heavy mineral assemblages [4,11,17,18], geochemical composition [5,6,19,20], magnetite content and other magnetic parameters [2,21,22] could also be applied to distinguish these two large rivers and the sediment provenance [4,5,17,23] of the Yellow Sea and East Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, projects needed to use stone, sand, gravel, cement and other building materials for slope protection as foreign majority and stone for embankment and geotextiles for dams [1][2]. But if the area relative lack of construction materials such as stone, the pipe-bag riding method is the other way in coastal protection and reclamation engineering [3][4][5][6][7]. Then, the material and damming method become the key problem since there is no rock material in the offshore area, the property of sand such as consolidation, shear strength and seepage must be discussed.…”
Section: Introductionmentioning
confidence: 99%